(untitled) (Journal of the College of Education for Women, 2019)
The civil war in Seralion is considered as complex model of internalconflicts in Africa because link to crises have relation to political, economical ,social and cultural conditions, which were infected by disability and paralysisin function performance, and what have effect on Seralion’s relationinternationally or regionally.In this research discussed three parts, the first is the factors of rise civilwar in Seralion , the second indicated the effected determiners in civil war inSeralion , the third shown the factors of put end to civil war in Seralion .The research concluded to significant reality that civil war in Seralion hadstrategic effects on regional or international relations .